Length of Resuscitation for Severely Depressed Newborns - Zhang, Stephanie Q.; Friedman, Hayley; Strand, Marya L. (American Journal of Perinatology, 2020)
Objective Current guidelines for neonatal resuscitation suggest it may be reasonable to stop resuscitation after 10 minutes in infants born with no detectable heartbeat. This study describes the length of resuscitation provided in a cohort of profoundly compromised newborn infants.Study Design Chart review of a regional hospital system database of newborn infants from 2010 to 2017 with a documented 10-minute Apgar score of 0 or 1.Results From a total birth population of 49,876 infants, 172 newborns were identified. Of these, 133 infants did not receive resuscitation and died while receiving comfort care. In the 39 resuscitated infants, 15 (38%) achieved return of spontaneous circulation (ROSC) at an average of 20 minutes; 32 of these 39 newborns (82%) died within 24 hours. Average time to ROSC for survivors was 17.8 minutes. Death or severe neurologic disability at 15 to 24 months of age was present in 92% (36/39) of resuscitated infants.Conclusion Prolonged resuscitation of newborns is rare. In this cohort, 92% died or had severe neurodevelopmental disability. Infants with ROSC received 20 minutes of resuscitation. Infants with ROSC typically did not survive beyond 24 hours unless they survived to discharge. To increase the number of infants with ROSC, continuing resuscitation beyond 10 minutes may be reasonable.
Keywords: resuscitation; newborn; asphyxia; neurodevelopment; prematurity; delivery room